Myocardial ischemia during ventilator weaning: a prospective multicenter cohort study - Bedet, Alexandre; Tomberli, Françoise; Prat, Gwenael; Bailly, Pierre; Kouatchet, Achille; Mortaza, Sater; Vivier, Emmanuel; Rosselli, Sylvene; Lipskaia, Larissa; Carteaux, Guillaume; Razazi, Keyvan; Mekontso Dessap, Armand (Critical care (London, England), 2019)
Background Weaning-induced cardiac pulmonary edema (WiPO) is one of the main mechanisms of weaning failure during mechanical ventilation. We hypothesized that weaning-induced cardiac ischemia (WiCI) may contribute to weaning failure from cardiac origin. Methods A prospective cohort study of patients mechanically ventilated for at least 24 h who failed a first spontaneous breathing trial (SBT) was conducted in four intensive care units. Patients were explored during a second SBT using multiple tools (echocardiography, continuous 12-lead ST monitoring, biomarkers) to scrutinize the mechanisms of weaning failure. WiPO definition was based on three criteria (echocardiographic signs of increased left atrial pressure, increase in B-type natriuretic peptides, or increase in protein concentration during SBT) according to a conservative definition (at least two criteria) and a liberal definition (at least one criterion). WiCI was diagnosed according to the third universal definition of myocardial infarction proposed by the European Society of Cardiology (ESC) and the American Heart Association (AHA) statement for exercise testing. Results Among patients who failed a first SBT, WiPO occurred in 124/208 (59.6%) and 44/208 (21.2%) patients, according to the liberal and conservative definition, respectively. Among patients with ST monitoring, WiCI was diagnosed in 36/177 (20.3%) and 12/177 (6.8%) of them, according to the ESC and AHA definitions, respectively. WiCI was not associated with WiPO and was not associated with weaning outcomes. Only two patients of the cohort were treated for an acute coronary syndrome after the second SBT, and seven other patients required coronary angiography during the weaning period. Conclusions This observational study showed the common occurrence of pulmonary edema in mechanically ventilated patients who failed a first SBT, but the association with cardiac ischemia and weaning outcomes was weak.